Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s10103-010-0778-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical evaluation of the influence of low-level laser therapy in secondary stability of implants in mice shinbones

Abstract: The present work evaluates mechanically the bone-implant attachment submitted or not to low-level laser therapy, with wavelength of 795 nm, in a continuous way, with power of 120 mW. The implant was placed in one of the shinbones of 24 mice, randomly distributed into two groups. The experimental group was submitted to six laser applications, divided into four points previously established, two lateral and two longitudinal, six times 8 J/cm2 with an interval of 2 days, totaling the dose of 48 J/cm2. The control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…Similar to findings described in previous studies, [8][9][10]13,14,18 our results showed enhanced bone growth around implants in all irradiated animals, although without significant difference from baseline values in all groups except E-20. This can certainly be attributed to the photobiomodulation action of LLLT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to findings described in previous studies, [8][9][10]13,14,18 our results showed enhanced bone growth around implants in all irradiated animals, although without significant difference from baseline values in all groups except E-20. This can certainly be attributed to the photobiomodulation action of LLLT.…”
Section: Discussionsupporting
confidence: 91%
“…[4][5][6][7] Experimental studies on the effect of LLLT on peri-implant bone healing have shown improved osseointegration and a shorter implant rehabilitation period. [8][9][10][11][12][13][14][15][16][17] The rabbit has been the preferred species for research on the process of osseointegration after LLLT. An advantage of rabbits over other animal models is that they are less aggressive, relatively inexpensive to purchase, and easy to house and maintain.…”
Section: Introductionmentioning
confidence: 99%
“…These procedures would not be possible in rats or mice. 9,10,13,40 In accordance with the most recent literature, LLLT was delivered by an infrared laser [7][8][9][10][11][12][13][14][15][26][27][28]35,38 of 830 nm wavelength 7,10,[12][13][14][15] and 50 mW output power in two sites near the mandibular implant, in seven sessions 7,11,12,15 every 48 h, using three different doses. The use of a sham surgery and sham LLLT control group (C-I), as well as a baseline surgery but sham LLLT group (C-II), enabled us to isolate both the influence of baseline surgery and the systemic effects of LLLT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the irradiation of extraction sockets, 3 modulation of skin wound healing, [4][5][6] regeneration of nervous tissue, 5 enhancement of peri-implant tissue repair after implant placement, 2,[7][8][9][10][11][12][13][14][15][16] and modulation of postoperative pain. 2,7,[17][18][19][20][21][22][23][24] Other in vivo and in vitro studies have reported the positive effects of LLLT on the repair process in animal models and tissue cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation